From brain-sparing to prioritised tumour growth: Insights into tumour-host interactions. - Dong, Q.; Cheng, L.Y. (Current Opinion in Cell Biology, 2025)
Cellular responses to their environment are shaped not only by genetic composition but also by interactions with neighbouring cells. Beyond local interactions, inter-organ crosstalk has emerged as a crucial mechanism coordinating tissue growth and function. In this review, we discuss recent findings, mainly using Drosophila as a model system to investigate how organs compete for resources under metabolic stress. This mechanism ensures the prioritized growth of essential organs during development and the growth of tumours at the expense of other tissues and host fitness. Together, these studies offered valuable insights into how inter-organ communications via secreted factors and host resource reallocation are important in affecting tissue fitness and driving disease progression.